A new species of Pseudogaurax Malloch (Diptera: Chloropidae) reared from dobsonfly egg-masses (Megaloptera: Corydalidae) in Brazil - Melo, Adriano S.; Wheeler, Terry A. (Zootaxa, 2009)
Pseudogaurax idiogenes Wheeler sp. n. (type locality: Iporanga, São Paulo, Brazil) is described from specimens reared from the egg masses of dobsonflies (Corydalidae) in southern Brazil. This is only the second record of Pseudogaurax larvae feeding on Megaloptera eggs (first from the Neotropical region). Larvae of most species of Pseudogaurax are predators of spider eggs.